Elluminate Artical: Lessons learned in researching virtual schools: The Newfoundland and Labrador experience - Michael Barbour (Athabasca University Press, 2007)
The publisher of IRRODL, The Canadian Institute of Distance Education Research (CIDER), is pleased to provide links to a series of online seminars that took place over Spring 2007, using Elluminate. These interactive CIDER Sessions disseminate research emanating from North America's and Canada's vibrant DE research community, and we feel these archived recordings are highly relevant to many in the international distance education research community. To access these sessions, you must first download FREE software from Elluminate (see http://www.elluminate.com/support/ )